2014
DOI: 10.1002/oby.20782
|View full text |Cite
|
Sign up to set email alerts
|

Dietary pulses, satiety and food intake: A systematic review and meta‐analysis of acute feeding trials

Abstract: Objective: To assess the effect of dietary pulses (beans, peas, chickpeas, lentils) on acute satiety and second meal intake, a systematic review and meta-analysis was conducted. Methods: MEDLINE, EMBASE, CINAHL, and the Cochrane Registry (through May 6, 2013) were searched for acute controlled trials examining the effect of dietary pulses on postprandial satiety or second meal intake compared with isocaloric controls. Two independent reviewers extracted data and assessed methodological quality and risk of bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 35 publications
3
55
0
2
Order By: Relevance
“…One mechanism may have been the satiating properties of dietary pulses (11,47,48). A recent systematic review and meta-analysis that evaluated 9 trials in 129 participants revealed a 31% increase in subjective satiety after a meal that contained dietary pulses compared with after a control meal, which was determined to be clinically meaningful (5). Dietary pulses may contribute to these satiety effects because of several physiologic properties, such as being high in fiber and protein and low in the GI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One mechanism may have been the satiating properties of dietary pulses (11,47,48). A recent systematic review and meta-analysis that evaluated 9 trials in 129 participants revealed a 31% increase in subjective satiety after a meal that contained dietary pulses compared with after a control meal, which was determined to be clinically meaningful (5). Dietary pulses may contribute to these satiety effects because of several physiologic properties, such as being high in fiber and protein and low in the GI.…”
Section: Discussionmentioning
confidence: 99%
“…4 Energy from carbohydrate:fat:protein intended for the intervention. 5 Negative energy balance refers to studies in which both dietary pulse and comparator arms were calorically restricted (i.e., weight-loss diets). Neutral energy balance refers to studies in which both dietary pulse and comparator arms had caloric intakes intended to meet their total energy needs (i.e., weight-maintaining diets).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Chickpeas, fed at 50 g available carbohydrates, compared to glucose drink as a control, had suppressed EI in healthy men at 120 min, but not when it was compared to white bread (Wong et al 2009); or when fed in bread as chickpea flour or extruded chickpea flour supplemented at 50 g available carbohydrate . Also, there was no effect of pulses reported by the meta-analysis of acute feeding studies on the suppression of EI (Li et al 2014).…”
Section: Food Intakementioning
confidence: 88%
“…Although, a meta-analysis study of acute research trials calculated a 31% increase in satiety AUC following legume consumption; nevertheless, this did not show any effect on the EI from the second meal (Li et al 2014). In fact, a range of factors can implicate the appetite responses and thus the subsequent food ingestion; for example, energy density, nutritional composition, the total volume of the preload, available carbohydrate and the inter-meal interval.…”
Section: Average Appetite and Associations Among The Outcomesmentioning
confidence: 96%